2017
DOI: 10.1016/j.colsurfb.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan cross-linked poly(acrylic acid) hydrogels: Drug release control and mechanism

Abstract: Chitosan has been used to cross-link poly(acrylic acid) to give three pH-sensitive hydrogels designed to control the release of the drugs amoxicillin and meloxicam. The extent of cross-linking and solution pH was found to dominate the swelling behavior of these hydrogels as shown by scanning electron microscopy and swelling time dependencies. The rates of release of amoxicillin and meloxicam from the loaded hydrogels increased with increase in pH consistent with the extent of hydrogen bonding between hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(87 citation statements)
references
References 45 publications
1
84
0
2
Order By: Relevance
“…Hydrogel materials are sensitive to pH reactions. A pH-sensitive hydrogel that was obtained by crosslinking chitosan with polyacrylic acid contained amoxicillin and meloxicam, and its release rate increased with increase of pH [102]. The methacrylic chitosan hydrogel swelled at a pH < 5, while it shrunk at a pH ≥ 7.4.…”
Section: Improving Of Chitosan Ph Sensitivitymentioning
confidence: 99%
“…Hydrogel materials are sensitive to pH reactions. A pH-sensitive hydrogel that was obtained by crosslinking chitosan with polyacrylic acid contained amoxicillin and meloxicam, and its release rate increased with increase of pH [102]. The methacrylic chitosan hydrogel swelled at a pH < 5, while it shrunk at a pH ≥ 7.4.…”
Section: Improving Of Chitosan Ph Sensitivitymentioning
confidence: 99%
“…Typically, PAA (0.1 m ), CaCl 2 (0.1 m ), and 5 mg of DOX were mixed in 10 mL of deionized water under gentle stirring for 1 h. Then, 10 mL of Na 2 CO 3 aqueous solution (0.1 m ) was quickly added into the mixture, and stirred for another 1 h resulting in the formation of DOX@ACC/PAA NPs. The formation of DOX@ACC/PAA NPs is driven by the electrostatic interaction and hydrogen bonding among DOX, PAA, and Ca 2+ . PAA chains bind Ca 2+ via electrostatic interaction, which prevents ACC from transforming into crystalline states after the addition of Na 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In the lower pH environment, the amount of exposed hydrophilic group was less, so the swelling ratio of KGM/GO hydrogels and KGM hydrogel do not have significant difference. However, with the increase in pH, some COOH group would convert to COO – group thereby enhancing the hydrophilic property of KG4 hydrogel and clearly improve its swelling ratio …”
Section: Resultsmentioning
confidence: 99%
“…From Figure (B), it was observed that the drug release behavior of KGM hydrogel in PBS 7.2 was different from that in 0.1 M HCl, due to the solubility of 5‐ASA in HCl and also the abundance of OH and COOH groups present in GO in HCl solutions. The immersion of KGM/GO hydrogels in 0.1 M HCl will result in transfer of more OH and COOH groups to the GO surface and a stronger hydrogen‐bond interaction, causing the drug release effect of KGM/GO hydrogels in 0.1 M HCl to be better than that in PBS 7.2. There is no significant difference in the release behavior of KG2 and KG4 hydrogels in PBS 7.2 and the release amount of 5‐ASA was about 77% after 22 h. Some drugs are easily dissolved in acidic media, thereby liable to cause stomach discomfort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation